2010
DOI: 10.5507/bp.2010.026
|View full text |Cite
|
Sign up to set email alerts
|

The Egsys and Oesil Risk Scores for Classification of Cardiac Etiology of Syncope: Comparison, Revaluation, and Clinical Implications

Abstract: Aims. EGSYS-U, EGSYS-M, and OESIL risk scores for syncope evaluation are introduced, evaluated retrospectively, and their ability to classify cardiac syncopes is compared. The specificity and sensitivity of the scores were analyzed. Guidelines for the practical application of the scoring systems are provided to reduce unnecessary hospital admissions.Methods. Retrospectively, 153 patients with syncope admitted to the Faculty Hospital in Ostrava in the year 2008 were enrolled for scoring with the EGSYS and OESIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…reported the sensitivity and specificity of OESIL model in predicting syncope patient outcome as 93% and 54.6%, respectively. [24] In addition, Ebell estimated the sensitivity and specificity of San Francisco model to be 98% and 56%, respectively. [25] As can be seen, the findings of the studies are contradicting in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…reported the sensitivity and specificity of OESIL model in predicting syncope patient outcome as 93% and 54.6%, respectively. [24] In addition, Ebell estimated the sensitivity and specificity of San Francisco model to be 98% and 56%, respectively. [25] As can be seen, the findings of the studies are contradicting in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The value of clinical findings and characteristics of syncope in prediction of patient outcomes have been evaluated in different studied [ 12 , 18 , 19 ]. In addition, various clinical decision rules have been designed and validated for this purpose [ 5 , 9 , 11 18 ]. Among them, EGSYS claims to be able to differentiate between cardiac causes and noncardiac causes of syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, EGSYS claims to be able to differentiate between cardiac causes and noncardiac causes of syncope. A study on 153 patients in 2008 showed that EGSYS is an efficient tool to distinguish cardiogenic syncope, reducing unnecessary hospitalization and improving ED management [ 18 ]. A study by Del Rosso et al in 2008 also demonstrated that EGSYS has high sensitivity in predicting cardiac causes of syncope [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Other study done by Plasek et al, states that EGSYS score >3 helps in prediction of cardiac etiology of cause of syncope. 29 There have not been many studies implementing this score in the emergency department for the identification of cardiac syncope. Comparing the correlation between severity and recurrence of syncope, 4 of patients with mild syncope had follow up repeat symptoms whereas 2 of pts with presyncope and 4 pts with severe syncope had follow up repeat symptoms.…”
Section: Palpitations Preceding Syncope -4 Pointsmentioning
confidence: 99%